(untitled) (Medical Forum Monthly, 2024)
Background: Geographical variation in the rates of kidney stones has been observed for many years. Pakistan is situated in stone belt. Calculus diseases is endemic in Pakistan, perhaps the incidence in Pakistan is highest in the world. Objective: To evaluate etiology and biochemical risk factors (inorganic Phosphate) in the Peshawar. Place and duration of Study: The study was carried out at Leady Reading Hospital, Hayatabad Medical Complex, Peshawar for the period of nine months. Patients and Methods: Study was conducted at LRH and Hayatabad Hospitals of Peshawar for the period of nine months. Two hundred patients and same number of controls were selected. Results: The mean value of mean inorganic phosphate in non stone formers were less than that of stone formers. The mean of urinary inorganic phosphate excretion in stone formers was greater than that of non-stone formers. Conclusion: We conclude that inorganic phosphate is an independent risk factor for renal stone formation.